The Teacher in Quarantine Time (Docentes 2.0 Journal, 2020)
The study process has been threatened in these times by the Covid-19 pandemic, like other activities, which is focused on virtuality. Teachers' concern about the sudden change in education has created an area of ??confusion because they have had to leave the physical classrooms digitally, that is, they feel a little afraid of violent change due to deficiency and ignorance of virtual tools at some educational levels. The objective of this essay tries to carry out a critical analysis on the attitude or posture of teachers in the use and adaptation of technologies, which has been affected by the Coronavirus, and which has generated discomfort in the educational environment due to a lack of technological infrastructure, deficiency in teacher training, and even deficiency of support from the Education Districts and therefore from the Ministry of Education of Ecuador in this context it is important to clarify that through this situation that the country is experiencing, it has been concluded that in the educational process of the different areas, there are deficiencies in knowledge and management of the use of digital platforms and virtual tools; This makes both educational and government institutions emphasize training and management of technological tools that help student training and strengthen the capacities of teachers.
Keywords: Teachers, Education, technology, computer assisted learning, internet